Surveillance of otitis media with effusion in thai children with cleft palate: Cumulative incidence and outcome of the management - Kitirat Ungkanont (2019)
© The Author(s) 2017. Objective: To study the incidence and outcome of management of otitis media with effusion in Thai children with cleft palate. Design: Retrospective cohort study in the tertiary care center. Patients: Ninety-five children with cleft palate were referred for ear evaluation, from June 1997 to January 2015. Fifteen children (15.8%) had associated craniofacial syndromic anomalies. Main outcome measures: Cumulative incidence of otitis media with effusion, rate of ventilation tube insertion, duration of indwelling tubes, hearing outcome, and complications of ventilation tubes. Results: Ear examinations were done every 8 to 12 weeks throughout the study. Cumulative incidence of otitis media with effusion was 53.7% in children within 12 months of age and 81.1% within 24 months of age. At the end of the study, all of the patients had at least 1 episode of otitis media with effusion. Eighty-eight children (92.6%) had palatoplasty, and there was no significant difference in the incidence of otitis media before and after palatoplasty. The mean hearing level at recruitment was 40.8 ± 18.4 dB. Ventilation tube insertion was done in 76 patients (80%). The median time for indwelling tubes was 11.7 months. Rate of ventilation tube insertion was 0.5/year. The mean hearing level at last follow-up was 23.5 ± 14 dB. Otorrhea through tube was found in 24 cases (31.6%). Conclusion: Otitis media with effusion was common in Thai children with cleft palate. Surveillance of middle ear effusion and ventilation tube insertion contributed to a favorable hearing outcome.